Impact of floating row cover and sensor placement on strawberry anthracnose and Botrytis fruit rot risk assessment. (10th January 2023) - Cosseboom, Scott D.; Schoeneberg, Anita; Lea‐Cox, John D.; Samtani, Jayesh; Johnson, Charles S.; Hu, Mengjun
Abstract: During the 2019–2020 and 2020–2021 growing seasons, six trials at four sites in Maryland and Virginia, USA were conducted, with leaf wetness and temperature sensors placed at 2 m height at the edge of the field (elevated sensor placement) or at the canopy level (0.5 m) on strawberry beds (canopy sensor placement). Temperature and leaf wetness duration (LWD) data from these sensors were used as input for anthracnose fruit rot (AFR) and Botrytis fruit rot (BFR) infection risk models, and fungicide spray trials were conducted to evaluate the ability of these predictions to control AFR and BFR. On average, the canopy level sensors reported significantly ( p < 0.05) longer LWD and higher temperature than elevated sensors during the fruit ripening period. The AFR and BFR risk calculated from the canopy sensors was also significantly higher than that from the elevated sensors. Fungicide spray programmes based on data from either canopy or elevated sensors resulted in fewer applications than weekly spray programmes, but the increased estimated risk based upon conditions within the canopy led to more applications than the elevated sensor treatment in four trials. In one trial with considerable incidence of BFR, plots that were sprayed based on the canopy sensor data controlled BFR significantly better than the elevated sensor spray programme. Springtime temperature, LWD, AFR risk and BFR risk were largely unaffected by autumn row cover deployment. The difference in temperature, LWD and AFR and BFR risk based on sensor placement warrants careful consideration of sensor placement when implementing a disease warning spray programme. Abstract : Longer leaf wetness duration and higher temperature and fruit rot disease risk if sensors were placed in the strawberry canopy rather than an elevated position shows importance of sensor placement.